Sinusoidal Obstruction Syndrome (SOS) in Multiple Myeloma with Renal Failure - Urvi A. Shah; Sengottuvel Viswanathan; Beamon Agarwal; Aditi Shastri; Ioannis Mantzaris; Murali Janakiram; Noah Kornblum; Ira Braunschweig; Amit Verma; Yang Shi; John Reinus; Olga Derman (Case Reports in Oncological Medicine)
SOS is a rare complication of stem cell transplantation and has significant morbidity and mortality. We present three cases of SOS and highlight underlying risk factors for its development, such as impaired clearance of alkylating agents (especially melphalan) in patients with renal failure and prolonged infection. Although, melphalan and cyclophosphamide cause SOS less commonly than alkylating agents such as busulfan, physicians must use caution when administering these drugs to patients with underlying comorbidities such as renal failure that may increase the likelihood of development of SOS. This is due to unpredictable pharmacokinetics in patients with renal failure and therefore close drug monitoring is required. With the recent FDA approval of defibrotide in 2016, outcomes of SOS have improved and physician awareness is important for prompt diagnosis and treatment.